Sputnik's guide to life on earth - Cottrell Boyce, Frank 1959- (Macmillan Children's Books, 2016)
The Blythes are a big, warm, rambunctious family who live on a small farm and sometimes foster children. Now Prez has come to live with them. But, though he seems cheerful and helpful, he never says a word. Then one day Prez answers the door to someone claiming to be his relative. This small, loud stranger carries a backpack, walks with a swagger and goes by the name of Sputnik. As Prez dithers on the doorstep, Sputnik strolls right past him and introduces himself to everyone in the household. Prez is amazed at the response. The family pat Sputnik on the head, call him a good boy and drop food into his mouth. It seems they all think Sputnik is a dog
Keywords: Human-alien encounters / Juvenile fiction; End of the world / Juvenile fiction; End of the world; Human-alien encounters; Children's stories; Children's fiction; Fiction; Juvenile works; Jugendbuch; Kinderbuch